New investigation of an E-mode metal-insulator-semiconductor AlInN/AlN/GaN HEMT with an Au-T-gate - Asmae Babaya; Adil Saadi; Seddik Bri (Universitas Ahmad Dahlan, 2021)
In a high electron mobility transistor (HEMT), the density of the two-dimensional electron gas (2DEG) channel is modulated by the application of a bias to a Schottky metal gate. These devices are depletion mode (D-mode), which means that a negative bias must be applied to the gate to deplete the electron channel and turn. The most challenging aspect in the present research activity on based-GaN devices is the development of a reliable way to achieve an enhancement-mode (E-mode) HEMT. Enhancement-mode GaN HEMTs would offer a simplified circuitry by eliminating the negative power supply. In this work, the aim is to investigate the different techniques which can influence the threshold voltage and shift it to a positive value. A novel E-mode metal-insulator-semiconductor (MIS) AlInN/GaN HEMT with an Au-T-gate has been investigated. The impacts of window-recess and deep-recess have been discussed, it was found that for dp=28 nm and wn=1.8 μm the threshold voltage achieves 0.7 V and the transconductance (Gm) peak value of 523 mS at Vgs=3.5 V. The drain current characteristic has been demonstrated.